Clinical profile of children mechanically ventilated in a pediatric intensive care unit of a limited resource setting - Anitha, G. Fatima Shirly; Lakshmi, S.; Shanthi, S.; Darlington, C. Danny; Vinoth, S. (International Journal of Contemporary Pediatrics, 2016)
Background: Mechanical ventilation, a lifesaving intervention in a critical care unit is under continuous evolution in modern era. Despite this, the management of children with invasive ventilation in developing countries with limited resources is challenging. The study analyses the clinical profile, indications, complications and duration of ventilator care in limited resource settings. Methods: Retrospective study of critically ill children mechanically ventilated in an intensive care unit of a tertiary care government hospital. Results: A total of 111 children required invasive ventilation during the study period of 1 year. Infants constituted the majority (68.5%), and males (59.5%) were marginally more than female children (40.5%). Respiratory failure was the most common indication for invasive ventilation (51.4%). The major underlying etiology for invasive ventilation was bronchopneumonia associated with septic shock (28.8%); and the same also required a prolonged duration of ventilation of > 72 hours (34.3%). Prolonged ventilator support of >72 hours predisposed to more complications as well as a prolonged hospital stay of >2 weeks and above, which was statistically significant. Upper lobe atelectasis (47.4%) and ventilator associated pneumonia (21.1%) were the major complications. The mortality rate of our study population was 36.9% as opposed to the overall mortality of 8.3%. Conclusions: Our study highlights that critically ill children can be managed with mechanical ventilation even in limited resource settings. The child should be assessed clinically regarding the tolerance to extubation every day, to minimise the complications associated with prolonged ventilator support. A favourable outcome requires good nursing care and meticulous management by an intensivist.